Prenatal sonographic characteristics and postnatal outcomes of umbilical-portal-systemic venous shunts under the new in-utero classification: A retrospective study. Issue 2 (January 2019) - Wu, Haifang; Tao, Guowei; Cong, Xiang; Li, Qi; Zhang, Jing; Ma, Zhe; Zhang, Zhonglu
Abstract : Abstract: An in-utero re-classification of umbilical-portal-systemic venous shunt (UPSVS) has recently been proposed. We retrospectively reviewed the sonograms of a large cohort of fetuses, identified and analyzed UPSVS cases, and presented the prenatal sonographic characteristics, birth outcomes, and follow-up results following the new classification system. Sonograms and clinical data of all participants who visited our departments from April 2016 to July 2018 were retrospectively reviewed. Identified cases of UPSVS were analyzed according to the new classification: Type I: umbilical-systemic shunt (USS); Type II: ductus venosus-systemic shunt (DVSS); Type IIIa: intrahepatic portal-systemic shunt (IHPSS) and Type IIIb: extrahepatic portal-systemic shunt (EHPSS). Postnatal follow-ups ranged from 3 months to 1 year. A total of 10 UPSVS cases were identified in 61, 082 fetuses: 4 with Type I, 3 with Type II and 3 with Type IIIa. All 4 cases of USS had complete agenesis of the portal venous system, and had the umbilical vein drained into the inferior vena cava. Two USS cases also had trisomy 21. Pregnancy was terminated in all cases with a Type I shunt. Two fetuses with DVSS had normal portal venous system and were born full term. The pregnancy of 1 DVSS case was terminated due to the detection of trisomy 21. Three cases were IHPSS with full-term birth. One had chromosomal abnormality and 1 had surgery to repair the shunt 12-days post birth. In the 2 cases that did not receive repair surgery, sonographic examination revealed the portal-hepatic venous shunt was not closed at the 6-month follow-up period. However, the 1 case that had repair surgery appeared healthy at the 3-month follow-up period. UPSVS is extremely rare. Type I shunts have the poorest prognosis, and the presence of the intrahepatic portal venous system is key to live birth in UPSVS regardless of types. Chromosomal abnormalities and other organ anomalies can occur in any types of UPSVS. Therefore, karyotyping and examination of other organs should be performed once UPSVS is detected.